Delivery and Prioritization of Surgical Care in Canada During COVID-19: An Environmental Scan - Seremi Ibadin; Mary Brindle; Tracy Wasylak; Jill Robert; Stacey Litvinchuk; Khara M. Sauro (Kerman University of Medical Sciences, 2023)
Background  During COVID-19 healthcare systems had to make concessions to make room for the surge of COVID-19 patients requiring hospital and intensive care. Postponing surgeries was a common strategy; however, it is unclear how surgical care was delivered during this time of constraint. The objective of this study was to understand how surgical care was delivered and prioritized during the COVID-19 pandemic response. Methods  This was an environmental scan following the Canadian Agency for Drugs and Technologies in Health methodology. This study was conducted in Canada; a universal, publicly funded healthcare system. Evidence sources on policies pertaining to the provision of surgical care between January 2020 and October 2022 were obtained from ministries of health, health services agencies and publicly funded hospitals across all 10 provinces and three territories. We synthesized the evidence sources using framework analysis. Results  We identified 205 evidence sources that described six themes about the provision of surgical care during the COVID-19 pandemic: the cycle of postponement and resumption; guidelines for triaging and prioritizing surgical cases; Infection Prevention and Control (IPAC), and safety measures for surgical care during COVID-19, patient-centred care, and looking forward (recovery planning, leadership, and decision-making). Conclusion  This study provides a comprehensive understanding of how surgical care was disrupted and innovated during COVID-19 which can inform future strategies for providing effective and efficient surgical care during times of healthcare constraint.